2009
DOI: 10.1161/circulationaha.108.826479
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Drug-Eluting and Bare Metal Stents

Abstract: Background-The safety and efficacy of drug-eluting stents (DES) among more generalized "real-world" patients than those enrolled in pivotal randomized controlled trials (RCTs) are controversial. We sought to perform a meta-analysis of DES studies to estimate the relative impact of DES versus bare metal stents (BMS) on safety and efficacy end points, particularly for non-Food and Drug Administration-labeled indications. Methods and Results-Comparative Conclusions-InRCTs, no significant differences were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(151 citation statements)
references
References 15 publications
5
134
1
11
Order By: Relevance
“…1,2 Although stents have essentially eliminated vessel reocclusion, restenosis has remained a costly and highly morbid problem. [3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process. 6,7 Coating stents with antiproliferative agents allows targeted delivery to the region of local trauma.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Although stents have essentially eliminated vessel reocclusion, restenosis has remained a costly and highly morbid problem. [3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process. 6,7 Coating stents with antiproliferative agents allows targeted delivery to the region of local trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent meta-analyses [45] of RCTs comparing DES with BMS reported similar rates of death, cardiac death, and non-fatal MI, but a significant reduction in the need for subsequent or repeat target vessel revascularization (TVR) with DES. In contrast, Kirtane et al [46], in an unadjusted analysis of 182 901 patients in 34 observational studies of BMS and DES, reported a significant reduction in mortality (HR 0.78, 95% CI 0.71 0.86) and MI (HR 0.87, 95% CI 0.78 0.97) with DES. After multivariable adjustment, the benefits of DES were significantly attenuated and the possibility that at least some of the clinical benefit of DES might be due to concomitant dual antiplatelet therapy (DAPT) could not be excluded.…”
Section: Percutaneous Coronary Intervention Withmentioning
confidence: 89%
“…In native vessels, DES significantly reduce angiographic restenosis and ischaemiadriven TVR [45,215]. In RCTs, no significant differences were observed in the long-term rates of death or MI after DES or BMS use for either off-label or on-label indications [45,46]. In non-randomized large registry studies, DES use may reduce death and MI [46].…”
Section: Drug-eluting Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] However, meta-analyses 4,5 and long-term followup data 6,7 demonstrated that DES improved morbidity but did not reduce mortality (compared with bare metal stents; BMS). Newer generation DES may solve the problems encountered with first-generation DES.…”
mentioning
confidence: 99%